Implantación del sistema contable en la distribuidora “Dalmark” de la ciudad de Tena periodo octubre - noviembre 2014 - Yánez Castillo, Gladys Margarita (2015)
The current research work titled, Accounting System Implementation at “DALMARK” Dispenser in the Tena City, period October-November 2014; was made with the purpose of use a convenient accounting system to the DALMARK Dispenser, because at the moment it does not have its financial transactions in an organized way; therefore it does not put in practice the standards and techniques that rule the accounting. Moreover this work was made taken into account the academic statutes of the National University of Loja. It was completed with the proposed objectives then it proceeded to develop a plan and an account manual according to requirements of the business and made all the accounting process from file collection, the preparation of the staring inventory, following with the development of diary book, mayorization, checking balance, work sheet, it ´proceeded with the settings giving the financial statements, the same which threw financial information showing the situation of the distributor. Finally to conclude that the accounting process was developed in the previously company and there was obtained as results the statements of financial position, of results and cash flow, real, which are useful for opportune decision making and to announce the economic and financial situation of “DALMARK” Dispenser, and there is a suggest to keep that accounting process in order to profit of the daily information